Five years in Second Life, or: Phonetically Augmented Virtuality in Second Life English as a Foreign Language - Sobkowiak, Włodzimierz (Scribd, 2012)
In this book I narrate some of my personal and professional experience of Second Life (SL), one of the few hundred Virtual Worlds now in existence. I mostly talk about my teaching of English-as-a-Foreign-Language (EFL) pronunciation in an educational community called Virtlantis. This pro-bono community service lasted four (school) years, from September 2008 to June 2012. I conducted 163 weekly meetings of 'Pronunciation with Wlodek Barbosa', with students from all over the (physical) world. In the book I report in detail on these meetings, as well as append thirty actual activity notecards used during the lessons. In those activities I used Phonetically Augmented Virtual objects (PAVed objects), i.e. interactive objects constructed in SL which contain some phonetic content in them, such as sound files, phonetic transcription, test questions about pronouncing problems, etc. My main argument in the book is that such PAVed objects, modeled on Augmented Reality found in the physical world, could provide some genuine added value in SL (language) teaching and learning. Learning with such objects could leverage situational/embodied teaching methods and techniques, which have been found to be especially effective in SL. It could help reify some abstract linguistic concepts, such as stress, syllable or juncture, into virtual 'tangibles' of especial appeal to kinesthetic and visually minded learners. Theoretically, this augmentation could be extended to all objects created in SL, so that the entire world would function as a linguistically augmented Multi-User Virtual Learning Environment (MUVLE). This kind of augmentation appears to add educational value to SL over and above what is possible in face-to-face classroom language teaching/learning in the physical world on the one hand, and on online e-learning platforms, such as Blackboard or Moodle, on the other. Other issues discussed somewhat less in-depth in my book include: SL educational affordances (especially learner immersion/presence), the key SL skills necessary for language teachers, EFL teaching and learning in SL (with particular emphasis on pronunciation) and my own life story in SL. The thirty lesson scripts available in the Appendix are of direct use to EFL pronunciation teachers and learners, whether in a virtual or physical world. Interested readers may go into SL for their own copies of my games and activities with PAVed objects. The book is illustrated with fifty snapshots taken in SL and showing various aspects of my life and work there: from private life, through PAVed teaching, to teachers' workshops and language education conferences. The principal message of the whole text is: Second Life is a wonderful virtual environment for foreign language teachers and students. With or without linguistic augmentation, it offers many unique educational affordances for fully immersed, situated, exploratory and collaborative learning.
Keywords: English as a Foreign Language; pronunciation; Virtlantis; Second Life; teaching; Virtual World